PERANCANGAN SISTEM INFORMASI PERSEDIAN OBAT BERBASIS WEB (STUDI KASUS : APOTEK CAMILO SEHAT SEJAHTERA) - Alvin Batchiar; Fabia Ridho Annasafy; Nabila Siti Aulia Parasyfa; Heri Haerudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The need for an accurate, complete and relevant information system is needed by a business entity, including in the health sector, namely at Camillo Pharmacy, but in the current system this has not been obtained optimally. In the current system, recording is still done manually, this causes difficulties for employees and owners in making reports on drug stock data, because of the increasing amount of drug data. The final result of this research is a pharmacy information system product. With the pharmacy information system created, it is hoped that data searches, making drug stock inventory reports can be done more easily and relatively quickly.